KAPITAL SOSIAL DAN PEMBANGUNAN DI INDONESIA - Miftahusyaian, Miftahusyaian (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Social capital related with collective value in the social network which is growth-develop as the implication of reciprocal relationship that occur therein. Collective value is naturally creating and maintaining social capital. Increases, decreases, or the survival social capital is depends on the collective values that exist in social network In short, social capital is recognized has great influence from economic development and poverty reduction. In Indonesia to dig and take the hidden social capital need to be knitted trust of each element of this nation. Trust is media and first step to bind